Classe hospitalar: acessibilidade na estrutura e organização para o atendimento do público-alvo da educação especial - Schmengler, Angélica Regina (2016)
This research is connected to Special Education Research Line of Post-Graduation Program in Education from Federal University of Santa Maria and is supported by Personal Improvement Coordination of Superior Level Capes. This study began from the approximation with the investigation object and the intention of better comprehension of lived environment. Thus, the objective is to verify how a Hospital Class in Santa Maria public hospital is structured and organized to educational attendance of special education scholar-patients, contributing to the accessibility in hospital environment. This research is delimited as qualitative of study case type, which observation of learning spaces and semi-structured interviews with the pedagogical coordinator, the students those work in Educational Sector, two mothers of scholars in health treatment are developed. To obtain more theoretical consistence, authors were explored, who approach Hospital Class, as Ceccim and Carvalho (1997), Fonseca (1999, 2015), Ortiz and Freitas (2005), Covic and Oliveira (2011), and works that bring the knowledge about accessibility and permeate this issue in educational context, as assistive technologies, adaptions of architecture, communication and attitudes, pedagogical and curriculum alterations as explained by Manzini (2007, 2014), Sankako, Oliveira, Manzini (2007); Deliberato (2007); Bersch (2013), Gonçalves (2013), Rocha (2013). Data found were treated by contents analysis, according Bardin (2011). Data shown that two boys received educational attendance between 2014 and 2015: a student with low vision and other with giftedness. It was verified that there were pedagogical and attitudinal accessibility on educational attendance of both scholars. So, the necessary materials for this student learning, the necessary adaptions, as well as curriculum and flexible practices were available. Although, the scholar with low vision do not demonstrates much interest about teach-learning, educational professionals always were available for this attendance. With respect to the scholar with giftedness, he was stimulated according his interests, developing his abilities in linguistics area, which resulted in written and publication of poesy book. Nevertheless, it was observed deficient aspects in relation of architectonic accessibility and communication inside hospital space, needing adaptions and more recourse to attend physical, audition and visual deficiencies. Professionals appointed the need of specific formation for these public due to Pedagogy course disciplines do not offers issues necessary for this attendance. Other aspect mentioned was the lack of incentive from government public sector about the offer of recourse and availability of special educator collaborating in hospital class sector. Although some aspects have been positive in relation to the educational attendance, it is necessary a reflection about improvements to promote the accessibility inside this hospital. It is hoped this work contribute to the universe of academic research about accessibility and, mainly, put questions and suggests that confirm the developed work with special education scholars in Hospital Class.